Mokslininkų informavimo problemos žemės ūkio mokslinės ir techninės informacijos sistemoje - Zinnkevičienė, Julija (Knygotyra, 1986)
Scientific and technical advance depends upon the rate the results of agricultural science are realized in practice. Some problems of informing scientists are considered in the system of Lithuanian scientific and technical agricultural information. Five services of research institutes are discussed there. There is also given an outline of their organization as well as the basis and resourses of informational service. Suggestions are given how to solve some problems.